Tobacco Use and Its Health Effects among Professional Athletes in Qatar. (29th November 2016) - Chaabane, Zaina; Murlasits, Zsolt; Mahfoud, Ziyad; Goebel, Ruben
Abstract : The objective of the study was to determine the effects of tobacco use on selected markers of health and lung function in professional athletes. A total of 108 male professional athletes participated in the study from ten ball game teams in the same sport league in Qatar (age = 26.4 ± 5.1 yrs, height = 190.6 ± 11.9 cm, and weight = 91.5 ± 16.4 kg). The athletes have been playing professionally for about 6.3 years on average. In addition to demographic and tobacco use status, the following clinical variables were measured: resting blood pressure, heart rate, FVC, F E V 1 sec, and PEF. The prevalence of tobacco use among the athletes was 27.7%. The FVC, FVC%, and F E V 1 % were significantly lower among the smokers compared to the nonsmokers (p = 0.003, 0.044, and 0.001, resp.). There were no significant differences between cigarettes smokers and nonsmokers in BP, HR, F E V 1, F E V 1 /FVC, PEF, and PEF%. Similarly, those who smoked shisha had lower F E V 1 % values as compared to those who did not smoke shisha ( p = 0.001 ) . The decrease of F E V 1 and FVC among smokers compared to nonsmokers is similar to what has been reported in the literature about other populations.